Simplifying Glycan Profiling through a High-Throughput Micropermethylation Strategy. (August 2020) - Shajahan, Asif; Supekar, Nitin T.; Chapla, Digantkumar; Heiss, Christian; Moremen, Kelley W.; Azadi, Parastoo
Glycoproteins play key roles in various molecular and cellular functions and are among the most difficult to analyze biomolecules on account of their microheterogeneity, non-template-driven synthesis, and low abundances. The stability, serum half-life, immunogenicity, and biological activity of therapeutic glycoproteins, including antibodies, vaccines, and biomarkers, are regulated by their glycosylation profile. Thus, there is increasing demand for the qualitative and quantitative characterization and validation of glycosylation on glycoproteins. One of the most important derivatization processes for the structural characterization of released glycans by mass spectrometry (MS) is permethylation. We have recently developed a permethylation strategy in microscale that allows facile permethylation of glycans and permits the processing of large sample sets in nanogram amounts through high-throughput sample handling. Here, we are reporting the wide potential of micropermethylation-based high-throughput structural analysis of glycans from various sources, including human plasma, mammalian cells, and purified glycoproteins, through an automated tandem electrospray ionization–mass spectrometry (ESI-MSn) platform. The glycans released from the plasma, cells, and glycoproteins are permethylated in microscale in a 96-well plate or microcentrifuge tube and isolated by a C18 tip-based cleanup through a shorter and simple process. We have developed a workflow to accomplish an in-depth automated structural characterization MS program for permethylated N/O-glycans through an automated high-throughput multistage tandem MS acquisition. We have demonstrated the utility of this workflow using the examples of sialic acid linkages and bisecting GlcNAc ( N -acetylglucosamine) on the glycans. This approach can automate the high-throughput screening of glycosylation on large sample sets of glycoproteins, including clinical glycan biomarkers and glycoprotein therapeutics.